Verb inflection in monolingual Dutch and sequential bilingual Turkish–Dutch children with and without SLI. Issue 4 (11th April 2013) - Blom, Elma; de Jong, Jan; Orgassa, Antje; Baker, Anne; Weerman, Fred
Abstract: Both children with specific language impairment (SLI) and children who acquire a second language (L2) make errors with verb inflection. This overlap between SLI and L2 raises the question if verb inflection can discriminate between L2 children with and without SLI. In this study we addressed this question for Dutch. The secondary goal of the study was to investigate variation in error types and error profiles across groups. Data were collected from 6–8‐year‐old children with SLI who acquire Dutch as their first language (L1), Dutch L1 children with a typical development (TD), Dutch L2 children with SLI, and Dutch L1 TD children who were on average 2 years younger. An experimental elicitation task was employed that tested use of verb inflection; context (3SG, 3PL) was manipulated and word order and verb type were controlled. Accuracy analyses revealed effects of impairment in both L1 and L2 children with SLI. However, individual variation indicated that there is no specific error profile for SLI. Verb inflection use as measured in our study discriminated fairly well in the L1 group but classification was less accurate in the L2 group. Between‐group differences emerged furthermore for certain types of errors, but all groups also showed considerable variation in errors and there was not a specific error profile that distinguished SLI from TD.